2018
DOI: 10.2147/jpr.s188795
|View full text |Cite|
|
Sign up to set email alerts
|

10 kHz spinal cord stimulation: a retrospective analysis of real-world data from a community-based, interdisciplinary pain facility

Abstract: ObjectiveTo evaluate clinical outcomes and health care utilization at 12 months post spinal cord stimulator (SCS) implantation compared with baseline and a matched sample of patients receiving conventional medical management (CMM) for the treatment of low back and lower extremity pain.PatientsA retrospective study of patients with at least 24 months of active treatment at an interdisciplinary community pain center between December 1, 2014 and December 31, 2017. Thirty-two patients receiving implantation of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 49 publications
4
64
0
Order By: Relevance
“…It is important to note that, excepting studies by DiBenedetto et al . and Al‐Kaisy et al ., the reductions in opioid use reported here were spontaneous, observational outcomes of the respective studies . It is therefore readily conceivable that pain treatment with 10 kHz SCS in conjunction with a targeted strategy to reduce conventional opioid use could achieve greater decreases and/or higher rates of abstinence than those reported here.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…It is important to note that, excepting studies by DiBenedetto et al . and Al‐Kaisy et al ., the reductions in opioid use reported here were spontaneous, observational outcomes of the respective studies . It is therefore readily conceivable that pain treatment with 10 kHz SCS in conjunction with a targeted strategy to reduce conventional opioid use could achieve greater decreases and/or higher rates of abstinence than those reported here.…”
Section: Discussionmentioning
confidence: 52%
“…These results were strengthened by the SENZA‐RCT trial in subjects with low back pain, which showed that 10 kHz SCS reduced mean back pain by 67% and leg pain by 65% for at least 24 months and was associated with a 19% reduction in daily opioid consumption after 12 months, whereas traditional SCS was associated with only 1% reduction in daily opioid consumption ( P = 0.014, difference between groups) . Retrospective reviews of real‐world data in patients with chronic back pain also found pain reductions in the range of 45–63%, as well as decreases in opioid requirements and increases in opioid abstinence …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The smaller of the two studies was conducted in a single center. DiBenedetto and associates compared opioid consumption and procedural volume in 32 patients receiving 10 kHz SCS plus conventional medical management (CMM) with 64 case‐matched controls receiving only CMM . The study found a decrease in MEDD from baseline to 12 months only among 10 kHz SCS + CMM patients (92.2 to 66.0 mg/d, P = .001, N = 21).…”
Section: Resultsmentioning
confidence: 99%